PENGASUHAN ANAK USIA DINI DI ERA NEW NORMAL PERSPEKTIF ISLAM - Anwar, Rosyida Nurul; Azizah, Nurul (Thufuli, 2020)
Early childhood activities in the new normal era change all habits in fulfilling children's rights which are usually done on normal days. Caring for children in the new normal era not only provides a sense of comfort and avoids children from deviant behavior, but parents are required to pay attention to children's health and safety activities so that they avoid exposure to viruses. The purpose of this study is to describe how Islam manages parents in raising children in the new normal era. The research method uses a literature study. The results showed that Islam regulates that in parenting children must involve the scope of faith, morals, worship, and muamalah. Parenting patterns are adjusted to the child's developmental stages. Caring for children in the new normal era is also carried out by providing programmed and continuous guidance as well as mentoring children at home so that children continue to get learning and children have strong characters, namely having praiseworthy behavior and having morals.